PENURUNAN MOTIVASI KERJA KARYAWAN AKIBAT BIAS PENILAIAN KINERJA PADA GENERASI Z DI SURABAYA - Lelli Kisdayanti; Nur Farida (Bajang Institute, 2025)
This study examines the impact of bias in performance appraisal on the work motivation of Generation Z employees in Surabaya. The research employed a descriptive quantitative method with data collected via questionnaires distributed randomly among employees from various industrial sectors. The results indicate that biases such as halo effect, leniency bias, and central tendency bias significantly reduce work motivation. This decline is closely related to perceptions of unfairness in the evaluation process. The study recommends implementing a more objective appraisal system, evaluator training, and improved communication between management and employees to enhance fairness and transparency in performance evaluations